Statistical Signature and Its Theoretical Implication in Hot Jupiter Population (Journal of Scientific Research, 2024)
Hot Jupiters, a special class of exoplanets, always draw attention due to their intriguing characteristics. In this paper, we have continued our endeavor to understand the distribution of hot Jupiter populations and the architecture of planetary systems through the statistical framework. Different techniques to discover hot Jupiters have been studied here, and current data suggested that the transit method has better chances of discovering light and short-period candidates. Relation between orbital eccentricity and other planetary parameters like mass and orbital periods have been investigated to support the existence of a discontinuity in planetary mass distribution at ~4 MJ. A low p-value in the KS test indicates the existence of two different populations of hot Jupiters having a possibly different channel of formation. We also discussed these statistical results' theoretical and empirical implications for dynamical evolution.